Food Proteins and Bioactive Peptides - Maria Hayes (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This book will look at the advances made in the generation, extraction, and characterisation of bioactive peptides from different food and gut protein sources, in addition to examining the increased potential and novel uses of these peptides in functional foods and pharmaceuticals for health. Novel extraction methods will be discussed along with protein identification methods and the application of peptides in gut health and in the prevention of diseases associated with metabolic syndrome, including diabetes, heart disorders, obesity, and inflammation.